Some aspects to consider for improving reproduction of blu - Pylkkö, Päivi; Koskinen, Nita; Sepponen, Juhani; Rekilä, Teppo (ru, 2005)
Blue fox (Alopex lagopus) is the most important species for fur farming in Finland. At present selective breeding is focused to large and heavy animals. Ten years ago average weight of blue fox female varied from 7 to 10 kg. Today individuals over 20 kg can be found. Results of this study indicate that the first year's litter size/i In this study we have shown that there are several aspects to consider for improving the blue fox breeding. The first year's litter size/female is important when breeding animals are selected. In addition the blue fox breed should be taken into consideration when improvement of litter size is sought. The season when breeding animals are chosen is as well important. The average body size of blue fox female at the time of artificial insemination has an effect to the litter size. However, these aspects for improving litter size/female need still to be further studied in order to establish the right means for fur farming. Fur farmers have been alerted since 1990, because number of vixens born has not been as expected. Mink (Mustela vison) has improved det "the liter size (1 vixen/artificially inseminated female) during the last 20 years (Fig 1, Tarhaajan kalenterit 1983 - 2003). However, the litter size of blue fox has stayed the same or decreased during the years 1983-2003 (Fig 1). Aim of the study was to " v ok